Can Corporate Social Responsibility Promote Employees’ Taking Charge? The Mediating Role of Thriving at Work and the Moderating Role of Task Significance - Yan, Aimin; Tang, Liping; Hao, Yingchun (Frontiers in Psychology, 2021)
There is growing evidence to suggest that employees’ perceptions of their employer’s corporate social responsibility (CSR) positively influences their attitude and behavior. An increasing number of scholars have called for further explorations of the microfoundations of CSR. To that end, this study takes the conservation of resources perspective to examine relationships and the perception of CSR by employees, considering areas such as thriving at work, task significance, and employees taking charge. By analyzing 444 questionnaires completed by employees in China and using the conditional process analysis to test a hypothesis, results showed that the association between employees’ CSR perception and taking charge is significantly and positively correlated, with thriving at work mediating the connection. We also found that task significance negatively moderates the mediating effect between CSR and taking charge, such that the lower the level of task significance of a job, the more positive the effect of CSR on taking charge via thriving at work. These findings have theoretical implications for micro-level CSR research and managerial implications for entrepreneurs.